A citation analysis of the University of the Philippines College of Science theses and dissertations (1990-1995) - Villaflor, Marie Antoinette 1960-
was to foreign materials published during 1981 through 1990. This fact has implications for budgeting of acquisitions funds. Collection development managers in sciences have to maintain large amounts of their budgets to support increasing serial costs.